Effect of passing training variations on the overhand pass on volleyball games - Gunawan, Sani; Muharam, Agum Amung (Universitas Suryakancana, 2022)
The purpose of this study was to determine the Effect of Variations on Upper Passing Exercises on Volleyball Passing Skills in Volleyball Extracurricular Students at SMP Negeri 3 Manonjaya Kab. Tasikmalaya. The method that the author uses is the experimental method. The population used in this study were extracurricular volleyball students at SMP Negeri 3 Manonjaya Kab. Tasikmalaya. The total population is 35 people. The sample was done randomly by lottery with a total of 20 people. Based on the results of hypothesis testingÂ Â using a statistical approach, the research hypothesis that the author proposes is: